KAJIAN SAAT PEMBERIAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL PADI ( Oryza sativa L. ): Pupuk Organik Cair, Padi, Mentik Wangi - Baktiar, Bagus; Ratna Nurhayati, Dewi; Siswadi, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
The research entitled Study of the Application of Liquid Organic Fertilizer on the Growth and Yield of Rice (Oriza sativa L.), research on rice with the Mentik Wangi variety was carried out in the rice fields of Dukuh Macanan Village, Jogosetran Village, Jogosetran Village, Kali Kotes District, from March to July 2023. This research aims to examine the effect of applying OREA brand liquid organic fertilizer on the growth and yield of rice (Oriza sativa L.). The experimental design used was a Complete Randomized Block Design (RAKL) with a single treatment factor which was repeated 4 times and 7 treatments. The liquid organic fertilizer used is the OREA brand. The observation data was analyzed using analysis of variance (ANOVA) and continued by concluding the anova table with a level of 5%. The parameters observed include; plant height, number of tillers in a cluster, number of productive tillers, number of grain in a cluster, weight of grain in a cluster, weight of dry milled grain per plot, weight of 1000 seeds. The results of the research showed that the use of liquid organic fertilizer did not show significantly different results, but the parameters of the number of productive panicles and the weight of milled grain per plot had a significantly different effect on the yield and growth of rice (Oriza sativa L.). Keywords:Liquid Organic Fertilizer, Rice, Mentik Wangi